Life in the undergrowth [videorecording (DVD)] - Attenborough, David, 1926- (BBC Video ; Distributed by Warner Bros. Entertainment, 2006)
David Attenborough guides the viewer through a miniature universe teeming with life, never normally seen, yet all around us. New technology reveals surreal vistas and their extraordinary inhabitants.